LESSONS LEARNED: Settler Colonialism, Development, and the UN Regional Training Centre in Vancouver, 1959-62. - Meren, David (BC Studies, 2020)
IN THE SPRING OF 1959, the UN press service and Canada's Department of External Affairs (DEA) announced that the "rivers, forests, cities and industries of western Canada and northwestern United States [would] serve as a laboratory in economic and social development for a new-type training center." (1) The Regional Training Centre for United Nations Fellows at the University of British Columbia would "enable trainees from underdeveloped countries to study and observe activities in fields such as hydroelectric power, water development, mining, forestry, land management, cooperatives, credit unions, social welfare, and public administration." (2) Press reports explained that the "unique international venture," involving the UN, the Canadian government, and UBC would be located in the Pacific Northwest because "in the past 50 years this area has experienced a most remarkable expansion of population and of economic development." (3) Infused with the postwar optimism associated with Canada's economic progress, British Columbia's resource boom, and international development, the announcement simultaneously highlighted and obscured a history and ongoing reality of settler colonialism and, more broadly, the extent to which Canadian participation in development assistance rested upon a foundation of Indigenous dispossession. This article explores how settler colonialism intersected with the UN's training centre at UBC, which is built on the territory of the Musqueam people. It uncovers what the Centre's origins and activities say about understandings of development after 1945, especially the Canadian dimension of this global history. Specifically, it interrogates development's pedagogical dimension. Situating "technical assistance" and efforts to identify best practices into the literature on imperialism and settler colonialism, it highlights how, notwithstanding progressive motivations, Canadian academic involvement in development efforts rested upon and reified settler colonialism at home and abroad. (4)